Analisis Kebijakan Pemerintah Kota Jayapura Dalam Pemberdayaan Orang Asli Port Numbay Di Sektor Usaha Mikro Perdagangan - Safiudin Safiudin; Qutsiyah Qutsiyah; Andryka Syayed Achmad Assagaf (Jayapangus Press, 2023)
The increasing number of non-Papuans moving to Jayapura resulted in the Port Numbay Indigenous People (OPN) as natives of Jayapura City unable to compete in the micro-trade business sector. The present research examines the Jayapura municipal government’s policy regarding the empowerment of OPN in the micro-trade business sector based on the principle of affirmation. This type of empirical juridical research is descriptive with a qualitative approach. Data collection techniques use observation, in-depth interviews, and literature studies. The result showed that the empowerment program not only gave priority to OPN but also all indigenous Papuans (OAP) without neglecting non-Papuans. Empowerment policy is in the form of providing reinforcement and protection. Strengthening policies are implemented by developing entrepreneurial competencies, providing capital assistance and facilities, and promoting local products. Protection policies take the form of providing traditional markets for OPN and OAP and prohibiting non-Papuans from selling traditional handicrafts and garden products with Papuan socio-cultural characteristics. However, its effectiveness has been limited because strengthening the ownership of various factors of production, distribution, and marketing in the protected business sector has not been carried out.